2013
DOI: 10.1108/00220411311300066
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of graduate students' information seeking behavior: a meta‐synthesis of the literature

Abstract: Purpose -The purpose of this review is to draw out patterns of information seeking behavior of graduate students as described in the empirical research published from 1997 to the present. Design/methodology/approach -A systematic search of databases for studies on information behavior and graduate students was employed in order to retrieve studies for a systematic review. Common themes that emerged from the literature were synthesized into a discussion of behavior patterns. Additionally a study quality analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
123
0
19

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 66 publications
7
123
0
19
Order By: Relevance
“…Jamali and Nicholas (2006) found that PhD students browse electronic journals more than senior scholars in physics and astronomy. Catalano (2013) concluded that although Masters and PhD students both use the web for information searching, the latter believe that references provided by faculty members are more reliable. Whitmire (2002) argued that the information seeking behaviour of undergraduate students could be different from that of graduate students and faculty members but they can have similar information seeking behaviour because some students used resources suggested by faculty members more than other references (Korobili, Malliari, & Zapounidou, 2011).…”
Section: Professions and Sciencementioning
confidence: 99%
“…Jamali and Nicholas (2006) found that PhD students browse electronic journals more than senior scholars in physics and astronomy. Catalano (2013) concluded that although Masters and PhD students both use the web for information searching, the latter believe that references provided by faculty members are more reliable. Whitmire (2002) argued that the information seeking behaviour of undergraduate students could be different from that of graduate students and faculty members but they can have similar information seeking behaviour because some students used resources suggested by faculty members more than other references (Korobili, Malliari, & Zapounidou, 2011).…”
Section: Professions and Sciencementioning
confidence: 99%
“…An examination of subject-specific studies reveals the diversity of information practices across the humanities, for example music research was examined by Dougan (2012) and Brown (2002), information practices in art history by Larkin (2010) and Beaudoin (2005), and the research of historians by Tibbo (2003) and Rhee (2012). Although Catalano's (2013) review study could not find agreement on consistent information behaviours among humanities researchers, Barrett (2005) has suggested that humanities graduate students do share common approaches to research and 'tend to initiate research projects in haphazard, serendipitous ways ' (p. 330). Research supervisors play a key role in supporting humanities graduate researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A thorough literature review of the information behaviour of humanities scholars has been provided by Case (2012). Catalano's (2013) systematic review of the information behaviour of graduate students includes the humanities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Las revisiones sistemáticas comenzaron a utilizarse sobre todo en el campo de la medicina, bajo el paradigma conocido como Medicina Basada en la Evidencia (MBE), si bien su aplicación se ha ido extendiendo a otros campos profesionales de los que no es ajeno el de Biblioteconomía y Documentación (ByD) (Xu y otros, 2015; Phelps y Campbell, 2012), siendo los bibliotecarios de ciencias de la salud los primeros en aplicar los principios basados en la evidencia (Koufogiannakis, 2012a) aunque su uso se ha extendido posteriormente a entornos académicos o programas educativos (Catalano, 2013;Urquhart, 2010).…”
Section: Introductionunclassified